Training Delivery and Evaluationfor a Government Regulatory Firm (C). Issue 1 (March 2018) - Karve, Shailaja; Aggarwal-Gupta, Meenakshi
Western State Electricity Regulatory Commission (WSERC) had launched a series of trainings to enhance the managerial capabilities of its employees. This case presents the challenges of designing and conducting trainings for a rapidly expanding small organization. In order to conduct the trainings, training groups were formed and a training plan was made to sequence the trainings based on the objectives and expected outcomes. Training modules incorporated a mix of methods such as lecture, presentation, videos, games, cases, activities, instruments and hand-outs. There were many hindrances to the implementation of the training programme as per the plan. New entrants to the firm were also made a part of the training groups without TNA. There were inordinate delays and interruptions that at times had to be escalated to the senior levels. Over a period of time, the trainings were appreciated but differences and challenges emerged causing roadblocks in the journey of WSERC to become a learning organization. This case focuses on the challenges faced by an organization when the commitment and buy-in from the employees is not sustained. It brings to the fore the role of senior management to have continued focus on any intervention.